Synthesis, surface modification and optical properties of Tb 3+-doped ZnO nanocrystals - Pereira, A.S. (2006)
We report the synthesis and characterization of colloidal nanocrystals consisting of ZnO doped with Tb3+ cations. Introducing the Tb3+ cations in ZnO nanosized hosts led to photoluminescent systems whose wavelength emission depends on the excitation line. Chemical surface modification of the doped ZnO nanocrystals associated with photoluminescence studies allows us to conclude that Tb3+ cations are located in the ZnO core.